The technique of intensity-modulated radiotherapy in the treatment of cholangiocarcinoma - Petera, Jiří; Papík, Zdeněk; Zouhar, Milan; Jansa, Jan; Odrážka, Karel; Dvořák, Josef (Tumori, 2007)
AIMS AND BACKGROUND: Conventional radiotherapy in inoperable cholangiocarcinoma is limited by radiotolerance of the surrounding tissues. The aim of our dosimetric study was an evaluation of intensity-modulated radiotherapy in the treatment of inoperable bile duct carcinoma. METHODS: Four patients with inoperable cholangiocarcinoma treated by self-expandable stent placed to the biliary tree and radiotherapy were studied. The rotational technique, conformal 3D BOX technique and intensity-modulated radiotherapy plan were compared. Dose volume histograms and the normal tissue complication probability concept were used for comparison. The stent was used for target motion verification. RESULTS: The intensity-modulated radiotherapy plans showed favorable dose distribution in planning target volume and remarkable sparing of organs at risk. CONCLUSIONS: The intensity-modulated radiotherapy technique in bile duct carcinomas deserves further research and clinical evaluation.
Keywords: stenty; kombinovaná terapie; Humans; Palliative Care; radioterapie s modulovanou intenzitou; Computer Simulation; žlučové cesty extrahepatické; Female; Radiotherapy Dosage; financování organizované; nádory žlučových cest; celková dávka radioterapie; Financing, Organized; lidé; Bile Duct Neoplasms; Cholangiocarcinoma; Stents; počítačová simulace; ženské pohlaví; Male; paliativní péče; Bile Ducts, Extrahepatic; cholangiokarcinom; Combined Modality Therapy; Radiotherapy, Intensity-Modulated; mužské pohlaví